Porównanie metod szacowania pozyskaniowych szkód glebowych na przykładzie rębnego drzewostanu bukowego - Kulak, Dariusz (Leśne Prace Badawcze, 2014)
The study determines the extent of soil disturbances occurring during mechanised harvesting operations in a beech timber stand and investigates whether applying different research methods can be used to classify, in a comparable way, forest areas with different levels of soil damage. In the analysed stand, felling and on-site processing were conducted with chainsaws, while extracting – using an farm tractor. After the completion of logging operations, visible soil disturbances on each sample plot were measured, including their area, volume and depth, and the value of five most common indicators of soil damage was calculated. The share of disturbed surface area, the volume of soil disturbances and different soil damage indicators allowed sample plots to be arranged in the same way according to increasing levels of soil damage occurring during harvesting. A different order was observed only in relation to the depth of the ruts formed. The similarity of the applied measures and classifications of soil disturbances indicates that all of the methods can be applied to make simple comparisons of the degree of soil damage. Because field trials are easy to perform, soil damage indicators based on a visual assessment of soil condition, without the need to take measurements, are worth recommending at first. A fuller picture of the level and nature of detected soil damage, however, can be obtained by taking into account the depth of the disturbance.